What is the probability of unexpected eruptions from potentially active volcanoes or regions? - Burgos, Vanesa (2022)
Since the start of the twentieth century, 101 potentially active volcanoes have produced their first Holocene eruption, as recorded in the volcanoes of the world (VOTW) database. The reactivation of potentially active volcanoes is often a surprise, since they tend to be less well-studied and unmonitored. The first step towards preparing for these unexpected eruptions is to establish how often potentially active volcanoes have erupted in the past. Here, we use our previously developed FRESH (First Recorded EruptionS in the Holocene) database to estimate the past regional Average Recurrence Interval (ARI) of these unexpected events. Within the most complete portions of the FRESH database, a FRESH (i.e., the first recorded eruption from a potentially active volcano) has occurred as frequently as every ~ 7 years in the Pacific Ocean region (~ 50 years of relatively complete record) and ~ 8 years in Izu, Volcano, and the Mariana Islands region (~ 150 years of relatively complete record). We use the regional frequency to estimate the annual probability of a FRESH at individual potentially active volcanoes in selected regions of Asia–Pacific, which ranged from 0.003 for Izu, Volcano, and Mariana Islands to 1.35 × 10−5 for Luzon. Population exposure around potentially active volcanoes showed that at volcanoes such as Kendeng (Indonesia) and Laguna Caldera (Philippines), more than 30 million people reside within 100 km of the summit. With this work, we hope to establish how often potentially active volcanoes erupt, while identifying which regions and which potentially active volcanoes may require more attention.